Die dimensies "eenheid" en "katolisiteit" in die ekklesiologie van die Nederduitsch Hervormde Kerk sedert Ottawa 1982 - Van Wyk, Tanya ca. 20./21. Jh. (HTS teologiese studies, 2008)
The dimensions “unity” and “catholicity” in the ecclesiology of the Netherdutch Reformed Church since Ottawa 1982 This article examines the current ecclesiology of the Netherdutch Reformed Church of Africa (NHKA) with reference to the extent to which the church understands unity and catholicity as biblical indicatives and imperatives. The article argues that the church’s understanding of unity and catholicity is prejudiced and influenced by the prominence the church awards to the tenet of an ethnic “peoples church” (“volkskerk”). This has lead to the NHKA’s ecumenical isolation. It is hence argued that the abolition of the church’s “ethnic church theology” will result in the abolition of its ecumenical isolation and will enable the NHKA to confess anew with the “church of all ages”, the “one, holy, apostolic and catholic Church”.